Peningkatan Kemampuan Literasi Siswa SMAN 1 Mulak Ulu Kabupaten Lahat - Santati, Parama; Zunaidah, Zunaidah; Putri, Melisa Ariani; Eogenie, Eogenie; Akagani, Apriyan; Sintia, Sintia (Penerbit Goodwood, 2024)
Purpose: To improve reading and writing skills to increase the critical thinking ability of students at SMAN 1 Mulak Ulu, Lahat Regency. Methodology/approach: This training was conducted at SMAN 1 Mulak Ulu, with a total of 25 students participating. The methods used were lectures, class discussions, field observations in the school area, and writing a short observation report. Reading activities were carried out independently by giving books to the students. Evaluation is carried out by assessing observation reports and collecting participants' responses regarding the training via Google Forms. Results/Findings: The participants were very enthusiastic about actively asking and answering the instructor's questions. Interactive activities were carried out in the form of field observations, reading books, writing a short observation report, and a summary of the book reading. Evaluation of the observation reports showed that 64% of the participants had good writing skills. On average, participants had good knowledge of linguistic rules, but their ability to summarize reading still needs to be improved. Most participants stated that this program made a very good contribution to improving their skills and knowledge of writing scientific papers and reading. Thus, this kind of training needs to be continued to improve students' critical thinking abilities. Limitations: The number of participants was relatively small and only in one school. Training is still limited to literacy, so it needs to be developed for other skills Contribution: This training is very useful for students to improve their literacy skills.